Ghana's commercial seed sector: New incentives or continued complacency? - Tripp, Robert; Mensah-Bonsu, Akwesi (International Food Policy Research Institute, 2013)
This paper examines the current status and recent changes in Ghana’s commercial seed system for field crops. It includes a review of present performance and an examination of the factors that might influence the course of seed system develop-ment in the near future. The paper is timely because a number of changes in policies, regulations, responsibilities, and commercial interests mean that this could be a period of significant transition for Ghana’s seed sector, perhaps marking an end to the stagnation and complacency that have characterized the sector for the past several decades.